The playdate : parents, children, and the new expectations of play - Mose, Tamara R. (New York University Press, 2016)
A playdate is an organized meeting where parents come together with their children at a public or private location to interact socially or 'play'. Children no longer simply 'go out and play', rather, play is arranged, scheduled, and parentally-approved and supervised. How do these playdates happen? Who gets asked and who doesn't? What is acceptable play behavior? Tamara R. Mose focuses on the parents of young children in New York City to explore how the shift from spontaneous and child-directed play to managed and adult-arranged playdates reveals the structures of modern parenting and the new realities of childhood.